Implementation of the Breastfeeding Counseling Guide for Working Mothers on Breastfeeding Practices until 6 Months - Fitra Duhita; Nofrida Pratistiyana; Diah Wulandari; Setiya Hartiningtyaswati; Shanty Natalia (STRADA : Jurnal Ilmiah Kesehatan, 2025)
Employment in mothers is a dominant barrier in breastfeeding practices, so breastfeeding support for working mothers is needed to promote the number of exclusive breastfeeding. Mention the urgency of the study. This study aimed to determine the effect of implementing the breastfeeding counseling guide for working mothers on breastfeeding practices until 6 months. The study was conducted using a quasi-experimental design to pregnant working mothers in Kota Yogyakarta.